Left Anterior Mini-Incision for Pulmonary Valve Replacement in a 12-Year-Old. Issue 2 (March 2020) - Vekstein, Andrew M.; Nellis, Joseph R.; Meza, James M.; Andersen, Nicholas D.; Haney, John C.; Turek, Joseph W.
A 12-year-old, 32 kg male with history of Tetralogy of Fallot status post repair at 8 days of life presented with progressive pulmonary insufficiency and left pulmonary artery stenosis. Surgical options were discussed, and the patient and his family elected to pursue minimally invasive pulmonary valve replacement with left pulmonary artery augmentation through a 5-cm left anterior mini-incision. The procedure was performed without complication, and he was discharged on postoperative day 3. At the time of his last follow-up, the patient was recovering well without evidence of pulmonary stenosis or insufficiency.